Seneca Valley Virus 2C and 3Cpro Induce Apoptosis via Mitochondrion-Mediated Intrinsic Pathway - Liu, Tingting; Li, Xiangmin; Wu, Mengge; Qin, Liuxing; Chen, Huanchun; Qian, Ping (Frontiers in Microbiology, 2019)
Abstract Seneca Valley virus (SVV) is the only member of the genus Senecavirus of the Picornaviridae family. SVV can selectively infect and lyse tumor cells with neuroendocrine features and is used as an oncolytic virus for treating small-cell lung cancers. However, the detailed mechanism underlying SVV-mediated destruction of tumor cells remains unclear. In this study, we found that SVV can increase the proportion of apoptotic 293T cells in a dose- and time-dependent manner. SVV-induced apoptosis was initiated via extrinsic and intrinsic pathways through activation of caspase-3, the activity of which could be attenuated by a pan-caspase inhibitor (Z-VAD-FMK). We confirmed that SVV 2C and 3Cpro play critical roles in SVV-induced apoptosis. The SVV 2C protein was located solely in the mitochondria and activated caspase-3 to induce apoptosis. SVV 3Cpro induced apoptosis through its protease activity, which was accompanied by release of cytochrome C into the cytoplasm, but did not directly cleave PARP1.